THE MICRO-ORIGINS OF BUSINESS CYCLES: EVIDENCE FROM GERMAN METROPOLITAN AREAS - Daniele, Federica; Stüber, Heiko (Review of Economics and Statistics, 2023)
How large is volatility due to large firms? We answer this question through both reduced-form analysis and a calibration exercise. First, we exploit time and spatial variation across German cities and show that higher concentration is associated with more persistent local business cycles, and local concentration Granger causes local employment volatility. From a business cycle perspective, we find evidence in favor of granularity-driven recessions only. Next, we calibrate a structural model along the lines of Carvalho and Grassi (2019) and find that the more fat-tailed productivity distribution in bigger cities crucially depends also on the higher probability that firms will grow.
CRIS-Team Scopus Importer:2023-01-27